A educação da mulher e a imprensa: o papel da revista jornal das moças na transformação/conservação social (1914- 1930) - Moraes, Patricia Canabarro Coelho de (2022)
This study aims to analyze the relation between female education and the press, based on publications in the magazine Jornal das Moças, which was destined specifically to the female audience . This entertainment magazine presents an idealized model of women which is a characteristic of the conservative and patriarchal society. From this point, we seek to understand how the press, through the magazine, acts in the process of transformation and/or social conservation within the context in which it is inserted, performing a formative function, as well as intends to identify the conception of woman and how she is represented in the pages of the magazine. The analysis carries out a documentary research, with the magazine being the primary source, which covers, as a time frame, the period from 1914 to 1930. Furthermore, it is a bibliographic review, from a secondary source, based on articles, dissertations, theses, books, etc. Our theoretical framework is also based on Saffioti (2004; 2013; 2020); Louro (1987; 1997); Perrot (2007); Priore (2004; 2020); Hooks (2021); Federici (2019; 2021), among others. Moreover, a target search was carried out for theses and dissertations, which had the magazine as their central object, accomplishing a state-of-the-art research in order to define the clipping and to direct the analyzes. It was possible to identify the pedagogical character of the press by attributing specific patterns and behaviors to the female gender, which naturalizes differences and promotes inequalities, in addition to presenting its educational and formative character. In view of that, we can conclude that the woman conception present in the magazine reinforces inequalities between genders, contributing to the maintenance and/or conservation of a certain social model - the patriarchy - based on male supremacy. The publications contained in the magazine do not aim to contribute to an effective social transformation, just as they do not tend to think of education from an emancipatory perspective, especially aimed at women. Therefore, the magazine appears as a response from more conservative social segments, which sought to rival feminism and the questioning of the role of women in Brazilian society, in addition to suggesting the insertion of women in a context of submission.